VD_FINDINFO Jug / 2010 / 55 vom 14. Juni 2010 - VD Tribunal cantonal (2010)
PARTAGESENS GÉNÉRAL, PRÉVOYANCE PROFESSIONNELLE SELON LA LPP, DIVORCE, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 142 al. 2 CC, 22 LFLP, 111 al. 1 LPA-VD